A Cross-Sectional Study on the Relationship Between Health Literacy and Family Involvement in the Care of Stroke Patients at Regional Hospital - Vivin Sulistiani; Hartono, Hartono; Pranata, Shafaat (Critical Medical and Surgical Nursing Journal, 2025)
Introduction: Stroke was a leading cause of mortality and disability globally, with a significant prevalence in Indonesia. Health literacy and family involvement played critical roles in stroke management. This study examined the relationship between health literacy and family involvement in the care of stroke patients at Regional Hospital.  Methods: A cross-sectional descriptive analysis was conducted with 35 family members of stroke patients, selected using consecutive sampling. The sample size was calculated with a formula where the margin of error is 17%. Data were collected using the Health Literacy Survey-Short Form (HLS SF Q12) and the Family Engagement Measure (FAME) questionnaire, both validated and reliable. Statistical analysis using Chi-square tests evaluated the relationship between health literacy and family involvement, with a significance threshold of p<0.05.  Results: The majority of respondents demonstrated high health literacy (57.14%) and high family involvement (77.14%). Research results also revealed that respondents with high health literacy also exhibited high family involvement (54.29%), whereas those with low health literacy had lower involvement (14.29%). Chi-square analysis indicated a significant positive relationship between health literacy and family involvement (p=0.000). Conclusion: The study demonstrated that improving family health literacy positively influenced their involvement in stroke care. Educational interventions to enhance health literacy are essential to promote effective, family-centered care strategies.